Educar ambientalmente: la multirreferencialidad como camino hacia la sustentabilidad (Ensayos) - Villarruel Fuentes, Manuel (2023)
Understanding and operating sustainability within the educational practice, linked to environmental education, requires an approach that overcomes the linear sense, making room for complex thinking as a model alternative, concretized in the curricular framework and in the didactic deployment that should characterize it. From this perspective, the objective was to examine the curricular possibilities of sustainability from a multi-referential perspective, as a way of access to complex thinking. For this purpose, we resorted to the analysis and conceptual interpretation, as well as to the operativity of the theoretical precepts on transdiscipline and curricular transversality, since they are the referents that currently best explain environmental education. The results show the instrumental and scientificist sense of the current curricular proposals within the field of environmental education, aimed at the decontextualized management of sustainability, focused on disciplines, showing the relevance and validity of transdisciplinary approaches, of a multi-referential nature. It is concluded in the need to transcend the current instructional curricular design of transdiscipline and the utilitarian sense of transversality as ways of access to sustainability, to approach it from multireferentiality, attending to the complex social framework that prevails in each educational institution, assumed as a community.